The Role Of Advocates In Upholding The Principles Of Justice In Judicial Institutions - Fauziah Lubis; Andli Arya Harahap; Angga Wira Yuda Tarigan; Audi Mutia Adrivia Nst; Azura Tasya; Da Cahara; Muhammad Kaharuddin (Fox Justi : Jurnal Ilmu Hukum, 2025)
The aim of this research is to examine the role of advocates in upholding the principles of justice in the judiciary , and the challenges they face . How important is the existence of advocates in the justice system in Indonesia, because advocates in carrying out their professions are free to enter all stages of the investigation process , police investigations , prosecutors and courts ( civil , criminal , administrative , labor , business competition , and so on ). An advocate can even provide legal advice and assistance to people who have legal problems outside the judicial process (non- litigation) resolution ). Thus , advocates as law enforcement officer play an important role in creating certainty , justice and legal benefits in the Indonesian justice system . The role of advocates is very important in upholding the principles of justice in Indonesian courts , especially in the adversarial justice system . Their main task is to protect clients ' rights and ensure that the legal process takes place fairly and transparently . What are the roles of advocates in upholding the principles of justice in the judiciary ? And what challenges do advocates face in carrying out their function to uphold justice ? This research uses a normative method that combined literature reviews to explore these dynamics . It is hope that the research results will provide a better understanding of how advocates can increase their effectiveness in upholding justice , as well as support the reforms needed to create a legal system that is fairer and more responsive to the needs of society . Thus , this research will contribute to a deeper understanding of the challenges and opportunities face by advocates in carrying out their profession in the modern era .